Mobile application system supported BUC students services and learning - Al Farsi G.; Jabbar J.; Tawafak R.M.; Malik S.I.; Alsidiri A.; Alsinani M.; Sulaiman H.B. (International Association of Online Engineering, 2023)
Smartphones and applications plays a significant role in learning and management systems. Mobile application system was usually demanded, especially college students are always looking for things that benefit them at a university, even though the current applications were efficient enough to achieve a high level of supporting students learning needs. In this research, there is a requirement to implement a new application system for student education service with an easy way of managing data for educational purposes to reduce and save the time for search of traditional methods. This research method is based on surveying with the students of Al Buraimi University College (BUC). The findings of this survey reveal a positive result when they used the new proposed model, thus the goal was achieved and as a result of this research a new mobile application was developed which replaces several applications. 2020, International Association of Online Engineering.